1995
DOI: 10.1136/adc.72.6.518
|View full text |Cite
|
Sign up to set email alerts
|

Clinical manifestations associated with human herpesvirus 7 infection.

Abstract: Human herpesvirus 7 (HHV-7) is a new herpesvirus recently isolated from CD4+ T cells. I Recently, we reported that HHV-7 was a causal agent for exanthem subitum.2 In this report, we examined the clinical manifestations associated with HHV-7, especially exanthem subitum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
43
0

Year Published

1997
1997
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(48 citation statements)
references
References 5 publications
5
43
0
Order By: Relevance
“…As regards the cases of serologically proven primary HHV-7 infection in Japanese children, in all three children a rising titer of low-avidity antibody to HHV-7 was accompanied by high-titer, high-avidity HHV-6 IgG antibody, and in agreement with others (25,27), it was found that primary HHV-7 infection normally occurs after infection with HHV-6 and is accompanied by a secondary response to HHV-6. Turning to serologically proven primary HHV-6 infection in Japanese children, in all six children we documented seroconversion with low-avidity antibody to HHV-6, but in two children there were significant titers of antibody to HHV-7.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…As regards the cases of serologically proven primary HHV-7 infection in Japanese children, in all three children a rising titer of low-avidity antibody to HHV-7 was accompanied by high-titer, high-avidity HHV-6 IgG antibody, and in agreement with others (25,27), it was found that primary HHV-7 infection normally occurs after infection with HHV-6 and is accompanied by a secondary response to HHV-6. Turning to serologically proven primary HHV-6 infection in Japanese children, in all six children we documented seroconversion with low-avidity antibody to HHV-6, but in two children there were significant titers of antibody to HHV-7.…”
Section: Discussionsupporting
confidence: 68%
“…Both viruses belong to the Roseolovirus genus of the betaherpesvirus subfamily of herpesviruses and show very similar biological behaviors: (i) after primary infection they are shed in saliva throughout life (14,16,18,26,33); (ii) primary infection with either virus causes exanthem subitum (roseola infantum) (25,35), a classical exanthematous disease of childhood; and (iii) primary infection with either virus has been associated with childhood neurological illness, particularly febrile convulsions (12,27,28,32), and the DNAs of both HHV-6 (12) and HHV-7 (20) have been detected in cerebrospinal fluid. Any study of the relationship between the two viruses and disease must therefore use diagnostic methods able to distinguish between primary HHV-6 and primary HHV-7 antibody responses.…”
mentioning
confidence: 99%
“…17,21 It is not known whether HHV-7 invades the central nervous system, although reports of complications linked to primary HHV-7 infection are increasing. 13,25 As reported elsewhere, 9 -11,13 at least 53% of the 15 showed a significant simultaneous rise in antibody titers to HHV-6 during primary HHV-7 infection. This phenomenon will be explained by antigenic cross-reactivities 2,8,22 between both viruses or by reactivation of HHV-6 in a latent form by HHV-7.…”
Section: Discussionmentioning
confidence: 84%
“…The frequency was 28% among 50 with febrile exanthem, comparable with the frequency reported recently by others, ie, 37% 10 and 31%. 13 A larger prospective cohort study will be required to know the precise frequency of primary HHV-7 infection in patients with febrile exanthem and that of febrile exanthem among primary HHV-7 infection in childhood. As suggested elsewhere, 7,9 -13,20 the present data also indicate that primary infection with HHV-7 occurs after development of ES, the primary infection with HHV-6, because 54% had a clinical history of ES and 87% had HHV-6 antibody at the acute stage of HHV-7 infection.…”
Section: Discussionmentioning
confidence: 99%
“…Cross-reactivity between HHV-6 and HHV-7 antibodies has been demonstrated (6,19,20,24), and an interaction between these viruses in vitro has been postulated (13). Although an indirect immunofluorescence assay (IFA) is commonly used to determine titers of antibody against these viruses, the inability of this assay to distinguish cross-reacting HHV-6 and HHV-7 antibodies is problematic.…”
mentioning
confidence: 99%